Structures of urban carbon cycle based on network indicators: Cases of typical cities in China. (1st February 2021) - Xu, Yun-Cheng; Li, Xin-Hang; Ren, Ke; Chai, Li-He
Abstract: The reasonable urban carbon cycle (UCC) is an important ecological unit for our cleaner and sustainable society. The study of the structures of the UCC is very instructive for cleaner urban construction. With Beijing, Tianjin and Nanjing as cases, we innovatively establish urban carbon cycle network (UCCN) and study the UCCN indicators, the similarities and differences of the structural characteristics of UCC in different cities are revealed. (1) All weighted and non-weighted UCCNs are tightly connected with large node degrees. Relatively, Beijing's UCCNs are more clustered than Tianjin. (2) Both Beijing and Tianjin's UCCNs are mature and have small-world characteristics. Relatively, Beijing's UCCN is more stable and has more obvious small-world effects than Tianjin. (3) For Beijing, Carbon absorbed during photosynthesis, Carbon stored in natural vegetation, Carbon emitted from respiration and so on are important UCCN nodes with high links. For Tianjin, Fossil energy consumption and industrial manufacture related nodes have high links, being the main driving node of UCC. (4) The node centrality of UCCN in Beijing is overall smaller than that in Tianjin. The betweenness centrality of Carbon input from energy is greater than that of other nodes for Beijing's UCCN. For Tianjin, Carbon absorption of crops has a large betweenness centrality. (5) In cluster analysis of the UCC, Beijing, Tianjin and Nanjing's UCCNs all have large node degrees for vertical carbon output and artificial carbon storage in common. Many differences also exist. Beijing has the least significant horizontal carbon input, while Nanjing has the less significant horizontal carbon output. For Tianjin, the most critical module is horizontal carbon input. Our results are instructive for comparative urban carbon management strategies of the studied cities. Network indicators and theories, as new avenues for analyzing UCC, should also be widely applied to the study of UCC in other cities and countries.